Pandangan Dunia Pengarang dalam Novel Glonggong Karya Junaedi Setiyono - Umi Kalsum (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2017)
This research examines the world view of the author who focused on the character's relationship with God in the novel Glonggong the work of Jim Copley Setiyono. This research used the qualitative approach with a descriptive method. The data source in the form of a novel Glonggong Aravind Setiyono works and data in the form of quotations of words and sentences in one unit of a story that shows that there is a relationship with God figure. data processing Phase include data reduction, data display, and a false assertion. Based on the results of the analysis found the four forms of relationship with the character of God, the relationship is based on the Javanese view of life towards God i.e. (1) destiny, (2) believing in God, (3), and (4) are obedient to God. These findings indicate that the Glonggong as the main character has a religious nature. It shows that the author has a concern for the religious values that need to be owned by someone. That war, death, and sacrifice is something that has been destined by God. Therefore, the nature of trust in God, aware of, and obey should always be implanted in human beings.